2023
DOI: 10.1111/jce.15822
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of idiopathic left fascicular ventricular tachycardia: Implications of false tendons for mapping and ablation

Abstract: Introduction The anatomical substrate for idiopathic left ventricular tachycardia (ILVT) remains speculative. Purkinje networks surrounding false tendons (FTs) might be involved in the reentrant circuit of ILVT. The objective was to evaluate the anatomical and electrophysiological features of false tendons FTs in relation to ILVT. Methods Intracardiac echocardiography (ICE) was conducted on patients with ILVT. The relationship of the FTs with ILVT was determined using electro‐anatomical mapping. Results Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 5 Some clinical observations have directly proved the clear relationship between PVCs or idiopathic VT and the left ventricular FTs by combining the finding of intracardiac electrophysiological study and ICE mapping during radiofrequency ablation. 2 , 6 It has been reported that FTs contain fibrous tissue, myocardial fibers, Purkinje fibers, and blood vessels. 7 Increased automaticity of Purkinje cells within muscle fibers and mechanical traction at the FT attachment site were speculated to be accounted for in the mechanisms of PVCs arising from FTs.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Some clinical observations have directly proved the clear relationship between PVCs or idiopathic VT and the left ventricular FTs by combining the finding of intracardiac electrophysiological study and ICE mapping during radiofrequency ablation. 2 , 6 It has been reported that FTs contain fibrous tissue, myocardial fibers, Purkinje fibers, and blood vessels. 7 Increased automaticity of Purkinje cells within muscle fibers and mechanical traction at the FT attachment site were speculated to be accounted for in the mechanisms of PVCs arising from FTs.…”
Section: Discussionmentioning
confidence: 99%